Secondary hemophagocytic syndrome after autologous hematopoietic cell transplant and immune therapy for neuroblastoma. Issue 11 (12th August 2019) - Epperly, Rebecca; Furman, Wayne; Hines, Melissa; Santiago, Teresa; Li, Ying; Madden, Renee; Mamcarz, Ewelina; Cervi, David; Federico, Sara; Triplett, Brandon; Talleur, Aimee
Abstract: Secondary hemophagocytic syndrome (HPS) has been described after autologous hematopoietic cell transplant (AutoHCT). We report two cases of secondary HPS after novel consolidation therapy for high‐risk neuroblastoma as part of an institutional phase 2 trial incorporating immunotherapy into a "standard" AutoHCT regimen. Both patients developed liver dysfunction beyond expected course of hepatic veno‐occlusive disease, coagulopathy, hyperferritinemia, and when evaluated, elevated soluble interleukin‐2 receptor and hemophagocytosis. These cases highlight the need for clinicians to have a high index of suspicion for immune‐related complications in patients receiving immune therapies.